Der Beirat in mittelständischen Unternehmen - Scheel, Robert F., LL.M. (UC Berkeley) (Nomos Verlagsgesellschaft mbH & Co. KG, 2023)
This book shows how middle-sized companies can benefit from an “Advisory Board“. Although not required by law, many companies can advantage by implementing an additional board into their corporate structure. The author illustrates reasons and motives for corporations to decide in favor of an advisory board. Types and functions of such councils are described as well as options for its implementation and their limits. The book also points out how to choose the best members to the board, their liability and the organization of advisory boards within the company. If the corporation follows the book’s advices it can thrive through an advisory board.